Physical and chemical alteration of Distichlis spicata L. cell walls with NaCl and water stress - Lopez-Gutierrez, Francisco, author; Hughes, Harrison G., advisor; McNeil, Michael, committee member; Ross, Cleon W., committee member; Towill, Leigh E., committee member (Colorado State University. Libraries, 1991)
Cultured cells of the halophytic grass Distichlis spicata adapted to grow in 500 mM NaCl (-25 bar) exhibited an altered growth physiology that resulted in slightly slower cell expansion and fully expanded cells with volumes only one-half to one-third those of unadapted cells. The reduced cell volume occurred despite maintenance of turgor pressures sometimes 2-fold higher than those of unadapted cells. Tensile strength as measured by a nitrogen gas decompression technique showed empirically that walls of NaCl-adapted cells were weaker than those of unadapted cells. Correlated with this weakening was a substantial change in the organization of the matrix polysaccharides; specifically, glucuronoarabinoxylan was more readily extractable, perhaps caused by a decrease in cross-linkages with phenol substances. Despite a 3-fold decrease in the amount of hydroxyproline and approximately a 2-fold increase in tyrosine, the quantity of insoluble protein and, the proportions of crystalline cellulose remained relative constant. Glycosidic linkage analysis of carbohydrates revealed little modification in the quantity and primary structure of the matrix polysaccharides as a result of NaCl (salinity) and polyethylene glycol 8000 (water deficit) stress. The study revealed that changes in the superstructure of glucuronoarabinoxylan are the primary determinant in the tensile strength of NaCl-adapted cells.
Covers not scanned.
Keywords: Grasses